Adopting artificial intelligence technology in the world of digital art / Assoc. Prof. Dr Azahar Harun ... [et al.] - Harun, Azahar; Tengku Harrffadzillah, Tengku Shahril Norzaimi; Mohd Fadil, Mohd Zaki; Ayob, Mohd Abqari (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The presence of Artificial Intelligence technology, better known as AI, is becoming increasingly significant in human life. Many technologists and experts believe that this phenomenon will profoundly change the way we communicate, learn, think, and work. There are even concerns that AI technology might take over various tasks and potentially replace careers, particularly those based on computer technology.